Erythema elevatum et diutinum in a young man coexisting with autoimmune polyglandular syndrome type 3 – case report - Tupikowska, Małgorzata; Chlebicka, Iwona; Maj, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction. Erythema elevatum et diutinum (EED) is classified as a variant of leukocytoclastic vasculitis. The etiology of this disease is unknown. Erythema elevatum et diutinum may coexist with several systemic disorders including hematologic and rheumatologic diseases as well as type 1 diabetes, thyroid diseases and other endocrinopathies. Autoimmune polyglandular syndromes (APS) are rarely diagnosed conditions characterized by the coexistence of at least two autoimmune endocrinopathies and non-endocrine autoimmunopathies. Objective. Presentation of a patient with EED coexisting with APS type 3. Case report. A 23-year-old male patient was admitted to our department due to nodular lesions lasting for 5 months, located on the extremities, which were diagnosed clinically and confirmed histopathologically as EED. In spite of skin lesions the patient suffered from diabetes mellitus type 1, hyperthyroidism, celiac disease, myopathy and idiopathic urticaria – abnormalities characteristic for APS type 3. Substantial clinical improvement was observed after systemic administration of dapsone and, due to upper respiratory tract infection, a few weeks of antibiotic therapy. Conclusions . We present this case due to the rarity of EED, especially coexisting with APS, and the good effect of therapy with dapsone and oral antibiotics.